ENGINEERING TOOLS FOR THE DEVELOPMENT OF A MATHEMATICAL SOFTWARE - Hernández Molina, Oscar Julián
This Working Paper will explain how the software engineering tools were implemented with the development of mathematical software, making this system competent enough to be implemented in the Nuestra Señora del Carmen Educational Institution, complying with quality standards appropriate and based on the curriculum of the 5th grade of primary school of the Ministry of National Education.   This system was developed in order for students to learn in a didactic and practical way each of the topics and solve the exercises for the 5th grade of primary school, allowing a measurement of student data, the use of the information and communication technologies (TICs) as software tools and traceability, looking at whether the system achieves continuous improvement with the students.